3E 2S Health Behaviors of the Elderly in Narathiwat Province under the Coronavirus 2019 Pandemic - Nawakaning, Rorbia; Cheleng, Napeesah; Salae, Hudaibah; Pengmak, Thaweeporn; Niltaya, Tippayawan; Tongnuang, Patcharawadee (Nursing Journal of The Ministry of Public Health, 2021)
This study aimed to investigate and compare the 3E 2S (Eating, Exercise, Emotion, Stop smoking, Stop alcohol drinking) health behaviors of the elderly in Narathiwat Province during the coronavirus 2019 (COVID-19) pandemic. The sample of 1,087 people aged 60 years and over living in Narathiwat Province were obtained from multistage random sampling. A questionnaire consisted of demographic data and the 3E 2S Health Behavior in the elderly parts, which were content validated by experts. The Cronbach’s Alpha coefficient was .81 for reliability. Data were analyzed using descriptive statistics, t-test, and one-way ANOVA. The findings revealed that the total score for 3E 2S health behaviors among the elderly in Narathiwat Province under COVID-19 pandemic was at a good level ( = 3.86, .59). Considering each aspect separately, the score for stop smoking and stop alcohol drinking were at a very good level ( =4.89 and 4.98; SD=.38 and .17, respectively). In addition, the score for eating, exercise, and emotion were at a good level ( =3.08, 3.55, and 3.59; SD=1.25, 1.50, and 1.26, respectively). Moreover, elderly who varied in education and their ability in the use of medication had a significantly different level of 3E 2S health behaviors among the elderly in Narathiwat Province